The impact of E-learning support through smart chatbots enhancing academic performance and happiness across educational platforms for secondary school students - Aljeraisy, Waleed Homou (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed to measure the impact of e-learning support through smart chatbots to promoting the academic performance and happiness across educational platforms. The research sample consisted of (72) students. The sample was divided into two experimental group and control group of (36) students per group representing the community of secondary school pupils of the General Directorate of Education in Jeddah City. The researcher's approach to data collection and results is the experimental, semi-experimental design curriculum used: a test obtained from the researcher's preparation, to measure the level of educational achievement and verify learning outcomes, as well as the analytical descriptive curriculum used: an identification tool to measure the level of happiness from the point of view of students when using smart chatbots. The results of the study showed that there were statistically significant differences in morale level (0.01) between secondary students' grades for the experimental group. The results also showed a marked impact to students' post-test score rate to experimental group and the study showed that the improvement experimental group score in the dimensional measurement increased by 22.8% after implement of smart chatbots through educational platforms. The results of the questionnaire also showed students' high happiness arround 89.3%. The research recommended the use and adoption of smart chat tools in education based on artificial intelligence applications, for their role in improving and developing cognitive skills that enhance and support students' academic achievement and raise their level of happiness.
Keywords: E-Learning Support; Smart Chatbots; Achievement; Happiness; Educational platforms